In Search of an Ideal Test for Diagnosis and Prognosis of Kala-azar (Journal of Health, Population and Nutrition, 2010)
The latex agglutination test (KAtex), direct agglutination test (DAT), and the rK39 immuno-chromatographicstrip test (dipstick test) were evaluated for their role in the diagnosis and prognosis of visceral leishmaniasis(kala-azar) in India. Sera and urine samples from 455 subjects - 150 confirmed visceral leishmaniasiscases, 160 endemic controls, 100 non-endemic controls, and 45 other febrile diseases - were includedin the study. The sensitivity of the KAtex, DAT, and rK39 strip test was 87% [95% confidence interval (CI)80-96], 93.3% (95% CI 88-100), and 98% (95% CI 93-100) respectively. The specificity of these tests was98% (95% CI 93-100), 93% (95% CI 87-100), and 89% (95% CI 82-97) for the KAtex, DAT, and rK39 striptest respectively. Fifty cases were followed up and subjected to the KAtex, DAT, and rK39 strip test after 30days of successful treatment. The DAT and rK39 strip test showed positive results in all the 50 cases whereasthe KAtex showed no positive reaction in any case. Based on the results, it is concluded that the sensitivityand specificity of the DAT and rK39 strip test are comparable but the greater convenience of use of thestrip test makes it a better tool for the diagnosis of visceral leishmaniasis in the peripheral areas of endemicregions whereas the sensitivity of the KAtex needs to be improved to promote its use as a first-line diagnostictest in the field-setting. It may be used for the prognosis of the disease as antigen becomes undetectablein urine after 30 days of the completion of the treatment. Alternatively, it can be used as an adjunct withrK39 for sero-epidemiological surveys.Key words: Diagnosis, Laboratory; Direct agglutination test; KAtex; rK39 strip test; Visceral leishmaniasis;IndiaDOI: 10.3329/jhpn.v28i3.5557J HEALTH POPUL NUTR 2010 Jun;28(3):281-285